Pengaruh Lingkungan dan Etika Kerja Terhadap Kinerja Pegawai Puskesmas Sakura Sungai Ambawang Kabupaten Kubu Raya - B1021141011, Vitriyanti (Jurnal Manajemen Update, 2020)
ABSTRACTThe study aims to determine the effect of the environment and work ethics on employee performance at the Puskesmas Sakura Sungai Ambawang in Kubu Raya Regency. This is type of research is a descriptive study. The data used in this study are primary data and secondary data. The population of this study is all employees in the Puskesmas Sakura Sungai Ambawang in Kubu Raya Regency and the sample used is 75 respondents with an explanation in Arikuntos explanation which states that if the population is less than 100 respondents, then the total sample is taken as a whole.The analysis technique used in this research is descriptive statistical analysis, multiple linier regression analysis and equipped with the validity, reliability, normality, linierity, heteroscedasticity, multikulinierity, F tes, t test and determination. The data were processed using SPSS version 22.0.The result of this study indicate that partially the environment and work ethics do not have a significant effect on employee performance. Whikw simultaneously the environment and work ethics have a significant effect on the performance of Pusekesmas Sakura Sungai Ambawang in Kubu Raya Regency.Key words: Working Environment, Work Ethics, Employee PerformanceDAFTAR PUSTAKAAlex S. Nitisemito. (2010). Manajemen Personalia Manajemen Sumber Daya Manusia. Edisi Ketiga. Jakarta: Ghalia Indonesia.Arikunto, S. (2006). Metodelogi Penelitian. Yogyakarta: Bina Aksara.Azwar, S. (2011). Reliabilitas dan Validitas. Yogyakarta: Pustaka Pelajar.Bangun, Wilson. (2012). Manajemen Sumber Daya Manusia. Jakarta: Erlangga.Danang, Sunyoto. (2013). Metodologi Penelitian Akuntansi. Bandung: PT Refika Aditama Anggota Ikapi.Departemen Kesehatan Republik Indonesia. (2011). Rencana Strategis Departemen Kesehatan. JakartaEdy, Sutrisno. (2011). Manajemen Sumber Daya Manusia. Penerbit: Jakarta Kencana.Fauzi, M. (2011). Etika Kerja dan Kinerja Karyawan Pada Garuda Plaza Hotel Medan. Jurnal Manajemen Universitas Sumatera Utara. Vol 2 No 1, pp 1-7.Ghozali, Imam. (2013). Aplikasi Multivariate dengan Program IBM SPSS 21 Update PLS Regresi. Semarang: Badan Penerbit Universitas Diponegoro.Hasibuan, M.S.P. (2007). Manajemen Sumber Daya Manusia. Jakarta: PT Bumi Aksara.Henry, Simamora. (2012). Akuntansi Manajemen. Jakarta: Star Gate Publisher.Istijanto. (2010). Riset Sumber Daya Manusia. Jakarta: Gramedia Pustaka Utama.Khasanah, U. (2010). Etika Kerja Sarana Menuju Puncak Prestasi. Yogyakarta: Cetakan Satu Harum.Mangkunegara, A. A. P. (2012). Manajemen Sumber Daya Manusia Perusahaan. Cetakan kesepuluh, Bandung: PT. Remaja Rosdakarya.Muzammil, A. (2014). Analisis Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Perawat RSUD Petala Bumi Pekanbaru. Jurnal Ilmiah Fakultas Ekonomi Riau, Pekanbaru, Indonesia. Vol 1 No.2.Nitisemito, A.S. (2010). Manajemen Personalia. Cetakan ke 9. Edisi ke 4. Jakarta: ghalia Indonesia.Nurlaila. (2010). Manajemen Sumber Daya Manusia 1. Penerbit LepKhair.Peraturan Menteri Kesehatan Republik Indonesia, No 75/MenKes/PER/2014, Tentang Pusat Kesehatan Masyarakat Tahun 2014.Puskesmas Sungai Ambawang. (2019). Profil PKM Puskesmas Sungai Ambawang 2019. Sungai Ambawang: Puskesmas Sungai Ambawang.Riduwan. (2010). Skala Pengukuran Variabel-Variabel Penelitian. Bandung: Alfabeta.Riza, H. (2013). Etika Kerja Terhadap Kinerja Karyawan Pada PT. Jasa Marga (Persero) Cabang Balmera Medan. Jurnal Manajemen Universitas Sumatera Utara. Vol 4 No , pp 1-1.Rosmawati, S. Ade Jermawinsyah. (2018). Pengaruh Etos Kerja, Disiplin Kerja dan Komiteman Karyawan Terhadap Kinerja Karyawan Pada Puskesmas ARO Kecamatan Muara Bulian. Jurnal Ilmiah Ekonomi dan Bisnis. Vol 9 No.2.Santoso, S. (2012). Panduan Lengkap SPSS Versi 20. Jakarta: Elex Media.Sedarmayanti. (2011). Tata kerja dan produktivitas kerja. Bandung: CV Mandar Maju.Siagian, Sondang, P. (2011). Manajemen Sumber Daya Manusia Edisi Pertama, Cetakan Kedua. Jakarta: Bumi Aksara.Sinamo, J. H. (2011). 8 Etos Kerja Profesional Navigator Anda Menuju Sukses. Jakarta: PT. Spirit Mahardika.Sonny, K. (1998). Etika Bisnis. Yogyakarta: Kanisius.Sugiyono. (2015). Metode Penelitian Kuntitatif, Kualitatif dan R&D. Bandung: Alfabeta, CV.Sutrisno, E. (2010). Manajemen Sumber Daya Manusia. Jakarta: kencana.Umam, Kaherul. (2012). Manajemen Organisasi. Bandung: Pustaka Setia.Umar, Husein. (2014). Metode Penelitian Untuk Skripsi dan Tesis Bisnis, Edisi Kedua. Jakarta: PT. Rajagraafindo Persada.Wibi, R.A. (2015). Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Kinerja Perawat Bagian Rawat Inap Pada Rumah Sakit Umum Daerah (RSUD) Petala Bumi Pekanbaru. Jurnal Manajemen Fakultas Ekonomi Pekanbaru Indonesia. Vol 2 No 1.Wibowo. (2010). Manajemen Kinerja. Jakarta: Rajawali Press.Wursanto. (2010). Manajemen Kinerja. Jakarta: PT. Rajagrafindo Persada.Yusniar Lubis, Bambang Hermanto, Emron Edison. (2019). Manajemen dan Riset Sumber Daya Manusia. Bandung: Alfabeta